Recycling of lake sediments as phosphorus fertilizer: promising results from a greenhouse experiment with six different sediments - Tammeorg, Olga; Kiani, Mina; Kalu, Subin; Nabavi, Sharifeh; Simojoki, Asko; Tammeorg, Priit (Elsevier, 2025)
Removing sediment from lakes is effective for restoration but involves high disposal costs. Repurposing these sediments as fertilizers could address phosphorus (P) shortages. Our study evaluated the fertilizing potential of sediments from Finnish lakes (Matjärvi, Kutajärvi, Kymijärvi, and Enonselkä) and two basins of Estonia’s Lake Peipsi (Peipsi and Lämmijärv). We conducted a greenhouse experiment with ryegrass growing in sand, by applying to sand either 25 kg ha−1 of mineral P fertilizer or sediments with the same amount of bioavailable P according to their iron-bound P content, and using sand without any P fertilizer as a negative control. We also tested soil amendments like lime, biochar, or arbuscular mycorrhiza to enhance sediment-derived P availability. Results showed ryegrass biomass and P uptake in sediment treatments were 126 % and 133 % of those without added P. Sediments provided P and other macro- and micronutrients, enhancing plant growth. Organic matter contributed additional P, except for Enonselkä and Lämmijärv sediments. Contrary to our hypothesis, plant P uptake occurred even from sediments with high iron to P mass ratios, suggesting hypoxic conditions contributed to P solubilization. Biochar and lime amendments increased plant biomass, particularly in the Kymijärvi treatment, to 106 % of those without amendment, and decreased zinc (Zn) uptake, important for avoiding Zn contamination. These findings highlight the dual benefits of sediment removal for lake restoration and as a substitute for mineral P fertilizers. Further research is needed to explore the long-term effects of using lake sediments as fertilizers and identify optimal practices for enhancing nutrient availability under field conditions.
Keywords: lake sediments; phosphorus recycling; sustainability; biochar; lime; Arbuscular mycorrhiza